Aspek – Aspek Rancangan Temperature & Humidity Controller Berbasis Internet Of Things (IoT) - Ihsan, Mursyid Al; Yasri, Indra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In the cultivation of oyster mushrooms, special care is needed because oyster mushrooms are susceptible to disease, so that fungal growth will be inhibited, one of which is temperature and humidity which can affect fungal growth. Current technological developments make it easier to carry out oyster mushroom cultivation treatments. That is by adjusting the temperature and humidity automatically in the cultivation room. With automatic temperature and humidity control can facilitate maintenance and minimize the failure of oyster mushroom production. In this paper, an Internet of Things (IoT) system is created by reading and adjusting the temperature and humidity conditions of the oyster mushroom kumbung. NodeMCU is used as a microcontroller integrated with WiFi module to connect to the database. The sensor used is DHT11 for temperature and humidity readings. The android application is made using the Web-based MITAPPINVENTOR. The temperature of the oyster mushroom kumbung is maintained between 24 - 28ºC with fan and lamp actuators. The humidity of the kumbung is kept above 80%. The results of oyster mushrooms using IoT have better quality than mushrooms without an Internet of Things (IoT) system. Oyster mushrooms look whiter and fresher with the Internet of Things (IoT). Keywords : Oyster mushroom, Temperature, Humidity, Internet of Things (IoT), NodeMCU.